2021
DOI: 10.1101/2021.05.23.21257686
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Addressing anti-syncytin antibody levels, and fertility and breastfeeding concerns, following BNT162B2 COVID-19 mRNA vaccination

Abstract: Objective: To determine whether antibodies against the SARS-CoV-2 spike protein following BNT162B2 (Pfizer-BioNTech) COVID-19 mRNA vaccination cross-react with human syncytin-1 protein, and if BNT162B2 mRNA enters breast milk. Methods: In this observational cohort study of female front-line workers with no history of COVID-19 infection, we amplified BNT162B2 mRNA in plasma and breast milk and assayed anti-SARS-CoV-2 neutralising antibodies and anti-human syncytin-1 binding antibodies in plasma, at early (1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…Finally, using human data we demonstrated that circulating anti-syncytin-1 antibodies do not rise following COVID-19 mRNA vaccination with either mRNA-1273 or BNT162B2. These findings support the mounting evidence that a syncytin-1-based mechanism of infertility is not supported by scientific observations [19,21]. This study is limited as we only interrogated the presence of anti-syncytin-1 in a total of 51 subjects.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Finally, using human data we demonstrated that circulating anti-syncytin-1 antibodies do not rise following COVID-19 mRNA vaccination with either mRNA-1273 or BNT162B2. These findings support the mounting evidence that a syncytin-1-based mechanism of infertility is not supported by scientific observations [19,21]. This study is limited as we only interrogated the presence of anti-syncytin-1 in a total of 51 subjects.…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, many women at this stage in the pandemic have conceived following both COVID-19 infection and COVID-19 vaccination, with no reports of reduced fertility. Despite the absence of supporting evidence [21,22], the link between the mRNA vaccines and infertility persists, undermining mass vaccination campaigns worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…We also report the detection of low quantities of intact BNT162b2 mRNA in the serum and breastmilk samples – in 71% and 13% of the mothers investigated respectively. Several recent reports have inconsistently documented the presence of vaccine mRNA in the serum and breastmilk of women after BTN162b2 vaccination ( 13 , 35 , 36 ). The presence of intact vaccine mRNA in both sample types in our study highlights the stability and persistence of the vaccine mRNA nanoparticle within the bloodstream which may lead to infrequent transfer into breastmilk.…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been shown in a few studies that vaccine mRNA is not present in milk samples after vaccination (17,18), or is only detected in very low levels in some cases (19), providing reassurance that risks of exposure to the breastfed infant are minimal. This study adds to the evidence that vaccine components are minimally transferred to human milk.…”
Section: Discussionmentioning
confidence: 99%